Magnetic solid‐phase extraction of benzoylurea insecticides in tea samples with Fe3O4‐hyperbranched polyester magnetic composite as sorbent. Issue 8 (6th March 2019) - Liu, Chaoran; Liu, Xinya; Marriott, Philip J.; Qian, Heng; Meng, Zilin; Yang, Zhirong; Lu, Runhua; Gao, Haixiang; Zhou, Wenfeng
Abstract: In this work, a method for the analysis of benzoylurea insecticides, including hexaflumuron, flufenoxuron, lufenuron and chlorfluazuron, in tea samples by high‐performance liquid chromatography with Fe3 O4 ‐hyperbranched polyester nanocomposite as the adsorbent for magnetic solid‐phase extraction was developed. The magnetic nanocomposite was prepared and characterized by infrared spectroscopy, vibrating sample magnetometry, and scanning electron microscopy. The as‐prepared nanocomposite was used as a sorbent for the extraction and preconcentration of pesticide residues in tea samples. The extraction and desorption conditions, including mass ratios of raw materials, amount of sorbent, pH value, extraction time, and desorption time, were investigated. Under the final conditions chosen for the analysis, good linearity was obtained for all the tested compounds, with R 2 values of at least 0.9979. The limits of detection were determined in the range of 0.15–0.3 μg/L. The recovery obtained from the analysis of tea samples with various spiked concentrations was between 90.7 and 98.4%, with relative standard deviations (n = 4) lower than 4.1%. Furthermore, the present approach was successfully applied to the quantitative determination of residues of benzoylurea insecticides in real samples.